The subject matter of phenomenological research: existentials, modes, and prejudices - Fernandez, A (Springer Netherlands, 2016)
In this essay I address the question, “What is the subject matter of phenomenological research?” I argue that in spite of the increasing popularity of phenomenology, the answers to this question have been brief and cursory. As a result, contemporary phenomenologists lack a clear framework within which to articulate the aims and results of their research, and cannot easily engage each other in constructive and critical discourse. Examining the literature on phenomenology’s identity, I show how the question of phenomenology’s subject matter has been systematically neglected. It has been overshadowed by an unending concern with phenomenology’s methodological identity. However, an examination of recent contributions to this literature reveals that a concern with articulating phenomenology’s subject matter has gradually increased, although such articulations remain preliminary. In light of this, I delineate, define, and illustrate three layers of phenomenological research, which I term “existentials,” “modes,” and “prejudices.” While the delineation of these layers is drawn primarily from classical phenomenological texts, they are defined and illustrated through the use of more contemporary literature. Following the articulation of this subject matter, I briefly consider some of the debates—both foundational and applied—that can be facilitated by the adoption of this framework.